ANALISIS PENGARUH DEBT DEFAULT, DISCLOSURE, DAN OPINION SHOPPING TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Verby Letisya; Okto Irianto (Musamus Accounting Journal, 2018)
Analysis of the Influence of Debt Default, Disclosure, And Opinion Shopping To Acceptance Of Going Concern Audit Opinion (Empirical Study On Textile And Garment Companies Listed In Indonesia Stock Exchange Period 2012-2016) The purpose of this research is to find out the influence of debt default, disclosure, and opinion shopping toward acceptance of going concern audit opinion. Debt default used current ratio, disclosure was measured by Wallace index, and opinion shopping was measured by dummy variable. While going concern audit opinion was measured by dummy variable. The number of population in this research is all textile and garment companies which is go public and listed in Indonesia Stock Exchange from 2012 until 2016 that is 17 companies. Sampling method used by researchers is purposive sampling there are 7 companies from 2012 until 2016 so that the total observation of this research as many as 35 objects of observation. The data used is secondary data. The analysis technique used is logistic regression with enter method and using Statistical Package for Social Sciences (SPSS) ver 25 application as test equipment. The result of this research shows that partially debt default has a significant negative effect on acceptance of going concern audit opinion, while disclosure, and opinion shopping do not have an effect on acceptance of going concern audit opinion. The test results simultaneously show that the debt default, disclosure, and opinion shopping have a significant effect on the acceptance of going concern audit opinion. Keywords: Going Concern Opinion, Debt Default, Disclosure, and Opinion Shopping